ANALISIS KEPATUHAN HUKUM DEWAN PERWAKILAN RAKYAT DAN PRESIDEN ATAS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 91/PUU-XVIII/2020 TENTANG CIPTA KERJA - M. Sadewa Rafie Aldiza; Dodi Haryono; Junaidi Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Constitutional Court Decision No 91/PUU-XVIII/2020 states that the Job CreationLaw is conditionally unconstitutional and still valid with a 2-year deadline for improvement.The follow-up to the court's decision is aimed at the DPR and the President should makeimprovements to Law Number 11 of 2020 concerning Job Creation. However, the actiontaken by the DPR is to make changes to the Law on the Establishment of Laws andRegulations, which is the advice of the judge who dissented opimion. Meanwhile, IndonesianPresident Joko Widodo issued Perrpu Number 2 of 2022 concerning Job Creation, thisexplicitly aborted the conditional unconstitutional status of Law No. 11 of the Year 2020About Job Creation.This research is a normative legal research. It is based on literature research thattakes excerpts from reading books, or supporting books related to the problem understudy. This study used secondary data sources consisting of primary, secondary, andtertiary legal materials. This study also used qualitative data analysis and produceddescriptive data.From the results of the research and discussions carried out, it is necessary to havean ideal system to improve the application of the Constitutional Court decision inaccordance with the principle of erga omnes. The results showed that to optimize theprinciple, cooperation efforts between the Constitutional Court and other state institutionsor adressat decisions are needed in implementing it. One of them is by directly appointingthe competent state agency in the consideration of the decision to follow up. This can becombined with the application of judicial deferrals and the granting of a deadline for theenforcement of judgments imposed on the adressats as a determinant representation of legalboundaries and certainty.